Systems-level characterization and transporter engineering in Saccharomyces cerevisiae for improved hydrocarbon tolerance - Chen, Binbin (2014)
Hydrocarbon alkanes, components of major fossil fuels, are considered as next-generation biofuels because their biological production has recently been shown to be possible. However, high-yield alkane production requires robust host cells that are tolerant against alkanes, which exhibit cytotoxicity. To tackle this toxicity issue, it is essential to understand molecular mechanisms of interactions between alkanes and microbial hosts. Based on these mechanisms, we can further develop microbial host strains with improved tolerance against alkanes. Therefore, in this study, we aimed to improve the tolerance of Saccharomyces cerevisiae, a model eukaryotic host of industrial significance, to alkane biofuels by investigating and exploiting cellular mechanisms underlying alkane toxicity. To this end, we first investigated the mechanisms of cellular response to alkane biofuels at a system level through transcriptome analyses. Transciptome analyses suggested that C9 and C10 induced a range of cellular mechanisms such as membrane transporters, membrane modification, radical detoxification and energy supply. Among these hypothesized mechanisms, we were interested in identifying plasma membrane transporters which possibly aid in alkane secretion, leading to improved tolerance. In support of this hypothesis, we then expressed the hypothesized native transporters and demonstrated that the expression of transporters - SNQ2 or PDR5 significantly improved cell tolerance against decane (C10) and undecane (C11) through maintaining lower intracellular alkane level. Other than native transporters, we further explored novel alkane transporters from oleaginous yeast Yarrowia lipolytica based on the observation that it utilizes alkanes as a carbon source. Similarly, the expression of identified heterologous transporters – ABC2 or ABC3 resulted in improved cell tolerance against decane (C10) and undecane (C11). Here, we demonstrated that transporter engineering - identification and expression of native and heterologous transporters led to significantly improved tolerance against alkane biofuels in S. cerevisiae. We believe that the results here provide valuable insights into designing microbial engineering strategies to improve cellular tolerance for highly efficient alkane biofuel production.